Elementary education in early second millennium BCE Babylonia - Gadotti, Alhena (Cornell University studies in Assyriology and Sumerology, 2021)
"Investigates the study of Sumerian by nonnative Akkadian speakers during the Old Babylonian period in areas outside major cities whose schools have been studied extensively. Provides transliterations and translations of 715 cuneiform school exercise texts"--